Usage of Silver Nanoparticles in Orthodontic Bonding Reagents - Janet Jisoo Lee; Meigan Niu; Zinah Shakir; Geelsu Hwang; Chun-Hsi Chung; Mark S. Wolff; Zhong Zheng; Chenshuang Li (Journal of Functional Biomaterials)
Fixed orthodontic appliances, which are cemented to tooth surfaces, complicate the maintenance of oral hygiene and create a rough surface that is favorable for bacteria attachment. Additionally, the presence of orthodontic appliances may conceive a unique environment that interacts with cariogenic microorganisms, fostering a distinct microbial ecosystem compared to that of the patients without orthodontic appliances, thus increasing the vulnerability of tooth surfaces to demineralization and caries formation. Silver (Ag) has shown strong antimicrobial effects and has been extensively investigated in the medical field. Here, we aim to review the antibacterial properties and potential side effects of silver nanoparticles (AgNPs) when incorporated into orthodontic bonding reagents. This valuation could contribute to the development of novel bonding reagents designed to prevent the formation of white spot lesions and caries during orthodontic treatments.